2022
DOI: 10.3389/fped.2022.1022268
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in ryanodine receptor 2 (RYR2) genes at c.12670G>T associated with focal epilepsy in a 3-year-old child

Abstract: BackgroundRyanodine receptor 2 (RYR2) encodes a component of a calcium channel. RYR2 variants were well-reported to be associated with catecholaminergic polymorphic ventricular tachycardia (CPVT), but rarely reported in epilepsy cases. Here, we present a novel heterozygous mutation of RYR2 in a child with focal epilepsy.MethodsAt the age of 2 years and 7 months, the patient experienced seizures, such as eye closure, tooth clenching, clonic jerking and hemifacial spasm, as well as abnormal electroencephalogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Finally, there is an emerging relationship between certain types of epilepsy and mutations in RYR2, another gene with a crucial role in calcium homeostasis and signaling. Two recent studies have identified novel RYR2 mutations in five children with benign epilepsy of childhood with centrotemporal spikes (BECTS) [13] and a child with focal epilepsy [14]. The unified models for ATP2B2, KDM5B, and RYR2 each receive significant signals from pLoFs, with overall p-values of 2.31x10 -7 , 7.3x10 -5 , and 2.65x10 -9 respectively.…”
Section: Application To Epilepsymentioning
confidence: 99%
“…Finally, there is an emerging relationship between certain types of epilepsy and mutations in RYR2, another gene with a crucial role in calcium homeostasis and signaling. Two recent studies have identified novel RYR2 mutations in five children with benign epilepsy of childhood with centrotemporal spikes (BECTS) [13] and a child with focal epilepsy [14]. The unified models for ATP2B2, KDM5B, and RYR2 each receive significant signals from pLoFs, with overall p-values of 2.31x10 -7 , 7.3x10 -5 , and 2.65x10 -9 respectively.…”
Section: Application To Epilepsymentioning
confidence: 99%